Isolation and characterization of microsatellite loci from the Giant Freshwater Prawn (Macrobrachium Rosenbergii) - See, Leng Min (2008)
The giant freshwater prawn, Macrobrachium rosenbergii, or locally know as udang galah has become the most popular freshwater prawn for commercial culture and a significant cash crop for many poor farmers throughout Asia and the Pacific region. Ninety microsatellite repeat sequences were successfully isolated from M. rosenbergii using the 5' anchored-PCR technique. BLAST analysis of the micro satellite marker flanking regions showed similarities towards expressed sequence tags (ESTs) in aquatic species. Sixty-two microsatellite primer pairs were designed with 29 perfect microsatellites, four were imperfect or interrupted microsatellites and the rest were compound microsatellites. Of these 62 single locus DNA microsatellite markers, 24 showed polymorphisms in the giant freshwater prawns of which four loci had dinucleotide, 16 trinucleotide, three tetranucleotide and one pentanucleotide core repeat units. Nine microsatellite primer pairs from the green-lipped mussel (Perna viridis) were successful in cross-amplifying the giant freshwater prawn genome. However, only four of these cross-amplified microsatellite primer pairs were reliable and used in this study. Hence, the levels of genetic variability in 12 populations of wild M. rosenbergii and one cultured population in Malaysia were evaluated by using 28 microsatellite loci. The number of alleles per locus ranged from 2 to 26 and the total observed heterozygosity ranged from 0.2618 to 0.7265. A high level of polymorphism was also detected in each of the wild M. rosenbergii populations by using five RAPD and four LP-RAPD primers which generated 191 bands ranging in molecular weights from 150 bp to 2100 bp in 11 populations. The cross-amplifications of 32 of the 47 newly developed microsatellite primer pairs in nine other prawn species showed the presence of many highly conserved regions among the prawn species tested. However, some of the microsatellite motifs in the nine species tested differed slightly from the originally designed microsatellite loci for M. rosenbergii. These newly developed microsatellite loci were used to assess the genetic diversity and relationships of eleven wild M. rosenbergii stocks.